(3ebGdI dLGdjfhS aj Cf bhi GdfaS JhGHY deRGL GdHOfs
(3ChdgG (B:s
(3bGd LGdjfhS deG aMUJ Yf GJHGY bhi GdfaS deRGL GdHOf eQGJ cKjQI s
(3BNQgG (B:s
(3cGf HYVge PG ZVH hHYVge YOje GdZVH hHYVge PG age hHYVge YOje Gdage s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGHYIs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3CNdGb JjehQ (B290) s
Keywords: (3GdadSaI hGdefWbs